2022
DOI: 10.3389/fpsyg.2022.1051128
|View full text |Cite
|
Sign up to set email alerts
|

Daytime naps and depression risk: A meta-analysis of observational studies

Abstract: BackgroundThe relationship between daytime napping and depression remains debatable. Thus, a meta-analysis in this study was conducted to evaluate the relationship between daytime napping and depression.MethodsThe PubMed, Embase, Web of Science, and China National Knowledge Infrastructure databases were searched up to February 2022, and the reference lists of the included studies were also retrieved. A random-effects model was used to estimate the combined effect size.ResultsNine studies with 649,111 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Regardless of the length of sleep, siesta is related to diabetes, obesity, epidemic stroke and myocardial infarction in elderly women ( 27 ). Regarding the relationship between napping and depression, studies have shown that nappers are slightly more likely to suffer from depression than non nappers, and daytime napping may be a secondary result or symptom of poor health and sleep disorders, which may be an independent risk factor for depression ( 44 ). In addition, an MR analysis study on identifying modifiable factors for preventing depression found that the trend of daytime napping in adults seems to increase the risk of depression ( 45 ), especially when napping for more than an hour ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the length of sleep, siesta is related to diabetes, obesity, epidemic stroke and myocardial infarction in elderly women ( 27 ). Regarding the relationship between napping and depression, studies have shown that nappers are slightly more likely to suffer from depression than non nappers, and daytime napping may be a secondary result or symptom of poor health and sleep disorders, which may be an independent risk factor for depression ( 44 ). In addition, an MR analysis study on identifying modifiable factors for preventing depression found that the trend of daytime napping in adults seems to increase the risk of depression ( 45 ), especially when napping for more than an hour ( 46 ).…”
Section: Discussionmentioning
confidence: 99%